Analisis Rasio Likuiditas, Rasio Solvabilitas dan Rasio Rentabilitas untuk Menilai Kinerja Keuangan Koperasi Serba Usaha Andini Mulyo Unit Boyolali - Yassin Zanardi; Novi Permata Indah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aims to assess the financial performance of the Multipurpose Cooperative Andini Mulyo Boyolali Unit. This observation of financial performance was carried out by researching the financial statements of the multi-business cooperative Andini Mulyo Boyolali in 2015-2019. The data analysis method used is a quantitative method with a descriptive approach. Aspects of the financial statements. that become the reference include liquidity ratios, solvency ratios, and profitability ratios. The results showed that from 2015 to 2019 the financial performance of the Multipurpose Cooperative. Andini Mulyo Boyolali unit was very good when compared to the Assessment. Standards of the Ministry of Cooperatives and SMEs RI 2006. This can be seen. from the value of the liquidity ratio which managed to achieve an average CR of 406, 6% and CS by 200%. Judging from the solvency ratio, the average DAR produced is 17% and the DER is 21%. Then the average of the last component, the Multipurpose Cooperative Andini Mulyo Boyolali, managed to achieve an BOPO of 77%. Kata Kunci: Liquidity Ratio, Solvency Ratio, and Profitability Ratio.